Implications of climate variability and change for African lake ecosystems, fisheries productivity, and livelihoods - Natugonza, Vianny; Musinguzi, Laban; Olokotum, Mark; Naigaga, Shamim; Ogutu-Ohwayo, Richard (Journal of Great Lakes Research, 2016)
Inland fisheries are important for nutrition, employment, and income, but climate variability and change are adding to other stressors, such as overexploitation, pollution, habitat degradation, and invasive species, to threaten their productivity as well as livelihoods of fisheries-dependent communities. Understanding the whole socio-ecological system to enable communities to adapt and build resilience is therefore vital. Here, we present results froma review of the responses of African lakes, fisheries productivity, and livelihoods to climate variability and change, and provide suggestions on required policy interventions to promote adaptation and build resilience. Changes in climate variables, especially temperature, wind speed, and rainfall have contributed to changes in lake water levels, loading, and recycling of nutrients. In somelakes, such disruptions in physical and chemical conditions have triggered changes in water quality, algae and invertebrate productivity, life history of fish, and contributed to shifts in fish community composition, proliferation of invasive aquatic weeds, and changes in parasite–vector–host interactions. Fish yield has either increased or decreased depending on climatic events,with the latter negatively affecting livelihoods, and forcing affected communities to adapt. Because adaptation strategies are location specific, and influenced by local conditions, many adaptation strategies have been unguided and have negatively affected fisheries. The responses of fisheries to climate change vary among lakes of different morphometric characteristics. There is need for consistent data to examine the direction and consequences of climate variability and change on fisheries and livelihoods of specific aquatic systems, and promote location specific adaptation and mitigation measures.
Keywords: Adaptation; Aquatic productivity; Climate change; Fisheries Livelihoods